1994
DOI: 10.1111/j.1439-0442.1994.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Halothane as an Anaesthetic in Camels

Abstract: Summary Halothane as an anaesthetic was evaluated in 12 adult camels, thiopentone being used as an induction agent. In six camels, clinical signs and haematological and blood biochemical changes were investigated while in other six haemodynamic, acid base and blood gas changes were monitored. The dose of thiopentone required to ensure intubation for halothane anaesthesia was 7.25 ± 0.33 mg/kg. A modified technique of tracheal intubation was found to be safe and quick. During halothane administration all anaest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
5
6
0
Order By: Relevance
“…Endotracheal intubation has been cited as being difficult in camels because of the narrow oral space (White et al, 1987), the spatula-shaped tongue with a well-developed dorsum, the wide epiglottis that overlapping the soft palate, and the presence of the palatine diverticulum (Singh et al, 1994). However, muscle relaxation and analgesia resulting from the xylazine and ketamine administration was helpful in the intubation of the camels in the present study.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Endotracheal intubation has been cited as being difficult in camels because of the narrow oral space (White et al, 1987), the spatula-shaped tongue with a well-developed dorsum, the wide epiglottis that overlapping the soft palate, and the presence of the palatine diverticulum (Singh et al, 1994). However, muscle relaxation and analgesia resulting from the xylazine and ketamine administration was helpful in the intubation of the camels in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…In another study, heart and respiratory rates have been reported to remain above the base values during halothane anaesthesia in camels with respiration being shallow and rapid (White et al, 1986;Singh et al, 1994). This increase in the heart rate might be attributed to the marked tachycardia caused by the induction with (Singh et al, 1994). A significant increase in respiratory rate during halothane anaesthesia has been also recorded in water buffaloes (Malik et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations